2011
DOI: 10.1097/mpa.0b013e3182148342
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Lymph Node Metastasis Spread in Pancreatic Cancer

Abstract: Pancreatic cancer frequently metastasized to distant LNs via a complex pathway and developed into systemic disease. Aggressive multimodality therapy, including neoadjuvant therapy, is essential to improve the long-term survival of patients at substantial risk of distant LN metastasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
66
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 18 publications
5
66
0
6
Order By: Relevance
“…[32][33][34][35][36] The extent of nodal involvement throughout the nodal basin has been investigated by just a handful of studies, showing that the incidence of nodal metastases in the anterior and posterior pancreaticoduodenal area (stations 17a-b and 13a-b), as well as along proximal SMA (station 14a-b) was 30% to 40%, far higher than in other stations. 15,16,37 This concept was confirmed in our study population, being the incidence of LN metastases along the SMA, within pN1 patients, as high as 55.2%. Station 14a-b metastases resulted to be an independent predictor of survival in all the 3 multivariate models constructed, with a hazard ratio ranging from 1.75 to 2.38.…”
Section: Discussionsupporting
confidence: 75%
“…[32][33][34][35][36] The extent of nodal involvement throughout the nodal basin has been investigated by just a handful of studies, showing that the incidence of nodal metastases in the anterior and posterior pancreaticoduodenal area (stations 17a-b and 13a-b), as well as along proximal SMA (station 14a-b) was 30% to 40%, far higher than in other stations. 15,16,37 This concept was confirmed in our study population, being the incidence of LN metastases along the SMA, within pN1 patients, as high as 55.2%. Station 14a-b metastases resulted to be an independent predictor of survival in all the 3 multivariate models constructed, with a hazard ratio ranging from 1.75 to 2.38.…”
Section: Discussionsupporting
confidence: 75%
“…However, the worse survival rates reported by several authors in patients with metastatic para-aortic LNs (PALNs) [59,61,63,81] has been used by the ISGPS [42] to justify the weakness of the indication to remove station 16b1. Although Kayahara and Sakai [56,82] were unable to find a significantly different survival rate for LN-positive patients with or without metastases to PALNs, several other authors confirmed a significantly worse prognosis for patients with metastatic PALNs [54,64,65], also in a multi-institutional series of 822 patients [83]. The preoperative diagnosis of metastatic PALNs can spare some patients surgery, but the accuracy of helical CT, MRI, EUS, and 18-FDG PET is unfortunately quite low [68][69][70][71][72][73][74][75][76][77][78].…”
Section: Proposal For a Standard Lymphadenectomymentioning
confidence: 94%
“…The choice becomes more difficult when it comes to stations 8, 9, 11, 12, 14 and 16. While it is generally agreed that 8a LNs should be removed [41,42], whether or not the same applies to 8p is a much debated issue [42]. Until more details become available on the incidence of metastases to 8p LNs, it is best to remove them, partly because 95.7% of the data reported on the rate of metastases to station 8 come from Authors who resect both 8a and 8p [14,31,32,56,60,62,64], and partly because this does not add to the surgical risk. Station 12 poses the same problem.…”
Section: Proposal For a Standard Lymphadenectomymentioning
confidence: 95%
See 1 more Smart Citation
“…Classification of pancreatic nodes has not been uniformly standardized, although pancreatic lymph nodes are generally divided into regions based upon their location around the pancreas and the areas of drainage of the pancreas: head/neck, body/tail, left side, or right side (reviewed in [25,26]). Studies correlating primary tumor location and lymph node involvement following resection have helped to identify the regional patterns and probabilities of lymph node metastasis, but more analysis will need to done for consistent accurate prediction of lymph node involvement [2730]. …”
Section: Introductionmentioning
confidence: 99%